Empirical Analysis of Fiscal Sustainability and Optimal Level of Debt in Pakistan - Sehrish Haleem; Awais Khan; Malik Adeel Ur Rahman (Budapest International Research and Critics University, 2020)
Through the current study it’s been tried to discuss that how fiscal sustainability is impacted by the debt which is taken by countries in order to push their economy towards prosperity and growth in Pakistan. Because the economy is considering vulnerable in terms of Public debt due to huge fiscal deficit in the economy. The ARDL approach is being applied by taking GDP as dependent variable while public debt, total revenues, government expenditures and interest rate are been taken as independent variable. The findings of the study suggested that there is strong and significant relationship exist between focused variables. Public debt is negatively associated with GDP in both short run and long run, while government expenditure give positive and significant relationship with GDP and interestingly total revenue give negative significant relationship in long run that supported the argument that the high revenues in developing nations inversely affects the investment that is pillar of GDP, so it adversely affected. The interest rate is positively significant in long run but in short run its negatively related with GDP because it affects cost of capital. The findings of study attract the attention of policy makers that we need either debt reduction strategies or either to minimize the gap between public revenues and public expenditures to promote sustain economic growth in the economy.